Analisis Efektifitas Manajemen Layanan TI Aspek Service Operation Menggunakan ITIL V3 pada Aplikasi Visualisasi Data Kepegawaian - Mastuti, Windari Tri; Amrozi, Yusuf (Syntax : Jurnal Informatika, 2024)
This research aims to optimize the accuracy and efficiency of data management in terms of staffing. The Personnel Data Visualization Application is used as an important part of the implementation of the modernization strategy of information system governance within the Department of Public Works Bina Marga (DPU BM) of East Java Province. This information system governance uses the ITIL V3 framework which focuses on the Service Operation Domain for the Personnel Data Visualization Application. Data and information are obtained from all employees who work in the Personnel Division. Data collection is done through direct observation and interviews to ensure the accuracy of the information obtained. The results of the research show that the Personnel Data Visualization Application shows operational convenience and improvement in decision making. The data visualization features make it easy to access and analyze information related to staffing in a clear and informative manner.